Repeat cryoablation as a redo procedure for atrial fibrillation ablation: Is it a good choice?. (19th May 2022) - Alvarez-Ortega, C; Solorzano, C; Barrera, A; Toquero, J; Martinez-Alday, JD; Grande, C; Rodriguez, A; Garcia-Alberola, A; Perez, L; Ferrero, A; Hernandez, J; Cozar, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Medtronic Inc. Introduction: Catheter ablation of atrial fibrillation, both cryoablation and radiofrequency pulmonary vein isolation, have demonstrated to be safe and effective techniques for treating symptomatic atrial fibrillation as a first procedure. However, about one in three patients may face a redo procedure due to AF recurrence. The most suitable technique for redo is unknown. Purpose: The aim of this study is to assess the efficacy of cryoballoon AF ablation as a redo technique in patients with prior cryoballoon or radiofrequency AF ablation. Methods: We analyzed a nation-wide real-world cryoablation registry (RECABA) and compared patients who were referred for a first cryoballoon AF ablation procedure with those who had previously undergone cryoballoon or radiofrequency pulmonary vein isolation. The primary endpoint was AF recurrence during the first year after a 3-month blanking period. We performed survival analysis and built univariate and multivariate cox regression models. Results: From 1742 patients, 1625 had a 12-month follow-up visit. 1551 (95.45%) underwent a first cryoballoon ablation, whereas 33 (2.03%) had a previous CB ablation performed and 41 (2.52%) a previous RF ablation. Mean age was 58.6 ±10.4 years and 511 (31.5%) were women. 463 (28.5%) had persistent atrial fibrillation and there were no major clinical differences between groups. Prior-CB group had a higher share of veins without electrogram visualization, with a median of 100% (IQR 75%-100%), compared to prior-RF group (median 67%, IQR 25%-75%) and first procedure group (median 25%, IQR 0%-50%). Kruskal-Wallis test Chi2=54.35, p<0.0001. 12-month Kaplan–Meier estimate of freedom from AF recurrence after the blanking period was 78.5% (95% CI 76.2% - 80.7%) in the first procedure group, 61.0% (95% CI 41.4% - 75.8%) in the prior-CB and 89.2% (95% CI 73.6% - 95.9%) in the prior-RF group. Log-rank test Chi2=17.49, p<0.0001. Multivariate cox regression analysis pointed female sex, persistent AF, and prior-CB ablation as independent predictors of AF recurrence. The adjusted HR for AF recurrence of prior-CB ablation vs first-CB ablation was 3.13 (95% CI 1.82 -5.40) and for prior-RF vs first CB-ablation was 1.01 (95% CI 0.51 – 1.97). Conclusion: Repeat cryoballoon AF ablation shows higher rates of AF recurrences compared to first CB procedures or after prior RF ablation. These data suggest that patients with AF recurrence after CB-ablation have worse arrhythmic outcomes and may benefit from other ablation techniques after a recurrence.